2004
DOI: 10.1056/nejmoa040325
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Cardiac Life Support in Out-of-Hospital Cardiac Arrest

Abstract: The addition of advanced-life-support interventions did not improve the rate of survival after out-of-hospital cardiac arrest in a previously optimized emergency-medical-services system of rapid defibrillation. In order to save lives, health care planners should make cardiopulmonary resuscitation by citizens and rapid-defibrillation responses a priority for the resources of emergency-medical-services systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
334
6
22

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 770 publications
(375 citation statements)
references
References 31 publications
13
334
6
22
Order By: Relevance
“…4) Because tracheal intubation and adrenaline administration have been shown to affect the outcomes of OHCAs [16,[20][21][22][23], we analysed the effect of the project on the outcomes of OHCAs managed prior to hospital arrival without tracheal intubation or adrenalin administration. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) Because tracheal intubation and adrenaline administration have been shown to affect the outcomes of OHCAs [16,[20][21][22][23], we analysed the effect of the project on the outcomes of OHCAs managed prior to hospital arrival without tracheal intubation or adrenalin administration. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). In this term, we had a larger number of OHCAs, and the interval between the call and the arrival on the scene was significantly prolonged, presumably due to unusually heavy snowfall in this winter.The use of ACLS, including tracheal intubation and adrenaline administration, has been shown to affect the outcome of OHCAs [16,[20][21][22][23]. We compared the outcomes between the two time periods for OHCAs managed prior to hospital arrival without prehospital ACLS procedures because the incidence of ACLS was higher after the project.…”
mentioning
confidence: 99%
“…A randomized control trial where patients either received advanced cardiac life support with intravenous drugs or ACLS without intravenous drugs demonstrated no difference in survival to hospital discharge. [37] Furthermore, another study[38] showed no difference in survival to hospital discharge after institution of ACLS training (consisting of the addition of endotracheal intubation and intravenous line administration of medications).…”
Section: Discussionmentioning
confidence: 99%
“…And the weakest link in the “chain of survival” was the rarity of bystander CPR. The incidence of bystander CPR was 32% in New York,11 21% in Detroit,12 15% in Ontario, Canada,13 28% in Japan,14 25% in Singapore,15 and 25% in the US CARES Registry in 200916 and 28.6% in 2012 8. Only approximately one in four patients with witnessed OHCA was receiving bystander CPR.…”
Section: Survival Of Primary Cardiac Arrests Was Unchanged For Decadesmentioning
confidence: 99%